Creating the "University experience": promotional and multimodal video productions in Scandinavian higher education - Hogne Lerøy Sataøen; Daniel Lövgren; Simon Neby (Taylor & Francis Group, 2023)
ABSTRACTPromotional videos produced by higher education institutions (HEIs) are an important medium for introducing new generations of students to HEIs and communicating their roles and purposes to the outside world. Despite the widespread use of such videos, research on their contents and implications is relatively sparse. This study addresses this gap by analysing videos from 12 Scandinavian HEIs. The study found that the videos aligned with the concept of the 'Promotional University 2.0', emphasizing an intention to 'aspire to more' and 'add to the real world', and portraying the university as an arena for play and joy. Three main categories of videos emerged: student-centred, market-centred, and organization-centred. The study also highlights the ideological implications of the representations, as they reflect the tension between traditional and commercialized views of the university. The results contribute to an understanding of how promotional videos shape the expectations of students and other stakeholders. This research is important as it helps us understand how HEIs communicate and represent themselves in the highly competitive marketplace of higher education. It also illustrates the incommensurability between higher education policies aiming to promote democratization and serve the public interest on the one hand, and the images of HEIs created by promotional multimodal content on the other.